Unexploited food production potentials of new varieties: evidence from hybrid maize production in western Ethiopia - Alene, A. (2007)
The question of whether the intended gains in food production from new varieties have actually been realized by poor farmers has received little or no attention in the literature. This paper used a stochastic frontier efficiency decomposition methodology to derive the technical, allocative and economic efficiency measures for a sample of hybrid maize producers in western Ethiopia. The results revealed considerable underexploitation of the yield and profitability potentials of hybrid maize and indicated that farmers could increase production by an average of 26% if they all adopted the recommended management practices. Furthermore, adoption of the recommended management practices coupled with optimum use of inputs, especially fertilizer, would enable the farmers to reduce production costs by an average of 39%. Education, provision of input credit, and timely availability of critical inputs are positively and significantly related to the efficiency of hybrid maize production.